WE MADE A DEAL, MY MILK DIMINISHED AND HE STOPPED BREASTFEEDING LITTLE BY LITTLE: STOPPING BREASTFEEDING THROUGHOUT THREE GENERATIONS - Isabel Cristina Pacheco Van der Sand; Joseila Sonego (Universidade Federal de Goias, 2002)
This is a study of case, with qualitative approach, which objectives are to know the practice ofstopping breastfeeding by mothers that have familial relationship, and to identify the influence of transmission ofinformation among generations in that practice. The data was gathered through life history, told by seven subjects,through open interviews. For the analysis of data was used the thematic analysis of MINAYO (1993). The studyevidenced that style that the woman feeds her children has relation with the learning among generations, the socialand economic conditions, the historic context and the experience of each woman.